Preservation of labile organic compounds is the pathway for carbon storage in a 23-year continuous no-till system on a Ferralsol in southern Brazil - Briedis, Clever; de Moraes Sá, João Carlos; Lal, Rattan; de Oliveira Ferreira, Ademir; Franchini, Julio Cezar; Milori, Débora Marcondes Bastos Pereira (Geoderma Regional, 2023)
No-till (NT) system has the potential to sequester soil organic carbon (SOC) in the topsoil and increase soil quality. However, SOC accumulation in the soil profile and the mechanisms for SOC stabilization in NT are still a matter of debate, especially for soils of the tropics. Therefore, this study was conducted to investigate the long-term effects of two tillage systems (conventional tillage – CT and no-till – NT) on chemical and physical mechanisms of SOC stabilization and how these are related to the accumulation of SOC in the soil profile. Soils were sampled (0–100 cm depth) from a long-term experiment (23 years) established on a Rhodic Ferralsol in southern Brazil. Soils under native vegetation (NV) were used as a baseline. Results showed that conversion of NV to agriculture decreased on average the SOC stock by 70.8 Mg ha−1 (−33%) in the 0–100 cm soil layer. Between tillage systems, higher SOC stock was observed under NT than that under CT in the 0–5 and 5–10 cm soil layers, resulting in higher SOC stock in the entire topsoil (0–20 cm) in the conservation system. In the subsoil (20–100 cm), SOC was similar for both tillage systems. Fourier-transform infrared spectroscopy showed differences in the C composition between the tillage systems; an accumulation of labile compounds in the uppermost layer was observed under NT, which resulted in a lower SOM aromaticity index under this treatment than that in soil under CT management. Adoption of NT increased the proportion of large macroaggregates (> 2.0 mm) in 0–5 cm soil layer, resulting in a greater mean weight diameter (MWD) than under CT. Principal component analysis (PCA) and correlation analysis of data for 0–20 cm soil layer showed that SOC stock is positively associated with labile compounds, the proportion of large macroaggregates, and MWD, and negatively with small macroaggregates, aromatic compounds, and aromaticity index. These results indicated that the pathway for SOC accumulation in the topsoil of NT is influenced less by selective preservation but driven by the maintenance of labile organic compounds, a process achieved by the low turnover of large macroaggregates in the NT system. [Display omitted] •No-till accumulates more SOC than conventional tillage in the topsoil layer.•SOC stock is similar in both tillage systems in the subsoil.•No-till increases large macroaggregates and labile C compounds.•SOC accumulation in soils of the tropics is not related to an increase in SOM aromaticity.•Labile C protected into macroaggregates is critical to SOC sequestration in no-till.